Radio measurements of the depth of air-shower maximum at the Pierre Auger Observatory - (:unkn) unknown (American Physical Society, 2023)
The Auger Engineering Radio Array (AERA), part of the Pierre Auger Observatory, is currently the largest array of radio antenna stations deployed for the detection of cosmic rays, spanning an area of 17 km2 with 153 radio stations. It detects the radio emission of extensive air showers produced by cosmic rays in the 30-80 MHz band. Here, we report the AERA measurements of the depth of the shower maximum (Xmax), a probe for mass composition, at cosmic-ray energies between 1017.5 and 1018.8 eV, which show agreement with earlier measurements with the fluorescence technique at the Pierre Auger Observatory. We show advancements in the method for radio Xmax reconstruction by comparison to dedicated sets of corsika/coreas air-shower simulations, including steps of reconstruction-bias identification and correction, which is of particular importance for irregular or sparse radio arrays. Using the largest set of radio air-shower measurements to date, we show the radio Xmax resolution as a function of energy, reaching a resolution better than 15 g cm-2 at the highest energies, demonstrating that radio Xmax measurements are competitive with the established high-precision fluorescence technique. In addition, we developed a procedure for performing an extensive data-driven study of systematic uncertainties, including the effects of acceptance bias, reconstruction bias, and the investigation of possible residual biases. These results have been cross-checked with air showers measured independently with both the radio and fluorescence techniques, a setup unique to the Pierre Auger Observatory.
Keywords: Cosmic ray showers; Cosmos; Radio emission